Identifikasi Kebutuhan Sistem Informasi Menggunakan Metode Ward and Peppard Terhadap Kedeputian Bidang Penanganan Darurat Pada BNPB - Andre Firza Setyananda; Aditya Rachmadi; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The National Disaster Management Agency (BNPB) is one of the institutions tasked with tackling disasters in Indonesia. BNPB is a government institution that has a main mandate as an organizer of disaster management through the functions of coordination, command and implementation. Based on regulation from President 8/2008 on the establishment of BNPB, placing BNPB as a non-departmental technical institution led by a minister-level head. In handling emergencies during disasters BNPB has a deputy for disaster emergency handling, whose task is to handle disasters. BNPB is an institution that requires an information system to help data collection and data recapitulation and services at BNPB. Because to make the right decision, the government needs fast and accurate data sometime after the disaster. The Ward and Peppard methods are used in this study, because they are adapted to the conditions of the organization. The Ward and Peppard method is a process of identifying a portfolio of Computer-based SI applications that will support the organization in implementing a business plan and realizing its business goals. In Ward and Peppard's method will help writers in analyzing the internal and external environment of the company's business, analysis of internal and external environment systems and information technology (IS / IT) so that the goals expected by BNPB's Deputy for Emergency Management.